The Effect of Hardiness Training on Academic Burnout in Nursing Students in STIKep PPNI Jawa Barat - Sudrajat, Diwa Agus; Rosmayanti, Wawat Wati; Kumala, Tria Firza (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: Academic burnout in nursing students is a result of academic demands, lack of interest, and incompetence, necessitating immediate action and hardiness training. Method: This study surveyed 50 nursing students with academic burnout using the MBI-SS questionnaire. The sample was randomly selected, and statistical tests included Wilcoxon nonparametric and Mann- Whitney. Results: There is a significant difference or influence on the scores before and after being given hardiness training with the Wilcoxon test results in the intervention group (Asymp. Sig. (2-tailed) = 0.000), there is an influence on the results of the Mann Whitney test after being given hardiness training in the intervention and control groups with the data results being (Asymp. Sig. (2-tailed) 0.002), which means that this research has a significant influence-because the Asymp. Sig. (2-tailed) < 0.05. Conclusion: Providing Hardiness training can reduce the level of academic burnout in nursing students.